(untitled) (ECO revista académica, 2024)
Coffeeconomics is an alternative field of economic research that can be used to evaluate coffee market structure behaviour from microeconomic and macroeconomic perspectives. The coffee market structure consists of the interaction of four large players: coffee producers (small, large and cooperatives), coffee brokers, coffee sellers (large, medium and small) and coffee consumers. The main objective of this study is to evaluate the vulnerabilities of the coffee market structure as a whole through the application of the National Coffee Production Function (NCP-Function). Finally, the NCP-Function of Guatemala was calculated in order to evaluate the risk and vulnerability of its coffee market structure between 1928 and 2018.